Recent advances in the application of ionic liquids in antimicrobial material for air disinfection and sterilization - Song, Xizi; Tian, Rujin; Liu, Kai (Frontiers in Cellular and Infection Microbiology, 2023)
Airborne transmission is one of the most unpredictable routes of infection. Nowadays, airborne diseases increase ever than before because of the complex living air environment. Apart from the inorganic particles, active microorganisms including bacteria, viruses, and fungi are incorporated in the pathogens acting as threaten to public health, which can hardly be treated by the traditional air purification methods based on adsorption. Therefore, effective filtration material with antimicrobial activity is demanded to solve the problem. Ionic liquids (ILs) are a category of salts that remain liquid at room temperature. The stable physico-chemical properties and extremely low vapor pressure make them suitable for a wide range of applications. Thanks to the numerous combinations of cations and anions, as well as the ability of inheriting properties from the parent ions, ILs are believed to be a promising industrial material. In recent decades, several ILs, such as imidazolium, pyridinium, pyrrolidinium, phosphonium, and choline, have been found to have antimicrobial activity in their monomeric or polymeric forms. This work focuses on the antimicrobial activity and safety of the latest types of ionic liquids, discussing the synthesis or manufacturing methods of ILs for air purification and filtration. Furthermore, possible applications of ILs antimicrobial materials in medical instruments and indoor environments are mentioned to encourage the scientific community to further explore the potential applications of ILs.